Discourse Analysis of Cosmetic Maybelline Advertising - Ni Putu Isha Aprinica (J-Lalite: Journal of English Studies, 2021)
The writing of words in print media advertisements is certainly influenced by the elements and structures of its own discourse. This study analyzes the elements and structures of cosmetic advertising discourse used by cosmetic manufacturers in promoting their products. The research approach used in this research is qualitative research by taking samples from Maybelline cosmetic advertisements contained in Seventeen Magazine 2012. Based on the analysis of elements and structures contained in Maybelline cosmetic advertisements, the elements used in the discourse of cosmetic advertisements are verbal elements and visual elements. while the structure of the discourse that appears is the opening, the content and the closing.